The O2 + NH3 Reaction Over Rh(110): Steady State Kinetics and Oscillatory Behavior - Rafti, Matias (2012)
The kinetics of ammonia oxidation with oxygen over a Rh(110) surface were studied in the pressure range 10-5 –10-4 mbar. Nitrogen was found to be the preferred product at low partial pressures ratios po2 : pNH3 , while the NO pathway was favored with oxygen rich gas mixtures and at high temperature. The reactive sticking coefficient of O2 reaches up to 0.05 under steady state conditions. Pronounced hysteresis effects in the reaction rates were found in T-cycling experiments. Sustained oscillations in the reaction rates occurred under isothermal conditions at T = 620 K at a total pressure of 4 9 10-5 mbar.